(untitled) (Journal of Parents and Teachers, 2012)
The study of the development and the intervention on positive emotions has not being an issue to deal with in scientific investigations until the 90s. The major trend back then was to study everything that could threaten the well-being of humans focusing on deficits and problems. The persons that develop their strengths and their capacities improve their quality of live and also prevent the appearance of disorders. Moreover, the perception of efficiency and well-being increase at the same time. This is the reason why we think this is very important. Also, it increases the sensation of happiness. Parents and teachers have the very important responsibility of focus their attention on the children’s capacity because it is the one that guides us to the deficits and limitations. This is a style that is possible to learn and after learning it, children will be able to recognize, use and develop their strengths not just in the present but in the future. ble to recognize, use and develop their strengths not just in the present but in the future.